Effect of Coriander Seed (Coriandrum sativum L.) as Diet Ingredient on Broilers Performance under High Ambient Temperature - Hamodi, Sunbul J.; Al-Mashhadani, Essa H.; Al-Jaff, Farah K.; Al-Mashhadani , Hanan E. (International Journal of Poultry Science, 2010)
This study was conducted to determine the potential effect of coriander seed as growth promoting substance in broiler chicks raised under summer condition in Iraq (32-36oC). One hundred and eighty day-old Arbor Acer broiler chicks were randomly assigned to four dietary treatments with three replicate pens (15 birds/pen). Birds were fed experimental diets containing 0% (T1), 1% (T2), 2% (T3) and 3% (T4) coriander seed. Water and feed were provided ad libitum during the experiment. Performance parameters were monitored weekly which include live body weight, weight gain, feed consumption and feed conversion ratio (g. feed/g. gain). Result showed that inclusion of 2% coriander seed in broiler diets improve (p<0.01) total means of live weight and weight gain. Further more, feed consumption and feed conversion were significantly (p<0.05) higher in the 2% (T3) coriander seed as compared with other treatments. Feeding broiler chicks 2% coriander seed as a diet ingredient resulted in a significant improvement in performance parameter. Therefore, inclusion of 2% coriander seed in broiler diets could be beneficial for improving broiler performance raised during summer months.